An Evaluation of the Educational Quality of a First Responder Course for Medical Students - Kiran Pandit; Aubrie Swan-Sein; Jane Kim; Aleksandr Tichter; Jeremy Sperling; Wallace Carter (Association of American Medical Colleges, 2013)
Abstract Introduction First responder training for medical students has not been evaluated in the literature. Columbia University College of Physicians & Surgeons (P&S) first-year students participated in a 4-hour first responder course with lectures and eight scenario-based small-group sessions, led by emergency medicine (EM) faculty and residents. The course goals are for students to achieve basic competence in responding to medical emergencies in nonclinical settings before emergency medical services arrive, and for EM residents to teach students. The evaluation assessed the educational quality of the course (effectiveness, efficiency, and appeal). Methods The students rotate through six small groups which are taught via scenarios in which the students are asked to act out their responses as "medical-student-on-scene," and critical points are taught by the instructors (emergency medicine residents and faculty) as the scene plays out. The six scenarios are: seizure, anaphylaxis, deformed extremity, stroke, choking, and chest pain with loss of consciousness. Results The evaluation assessed the educational quality of the course (effectiveness, efficiency, and appeal). Course effectiveness was assessed with both a one-group pre- and posttest design and a course evaluation questionnaire. Students responded correctly to 73% of pretest and 93% of posttest questions, a statistically significant difference (paired-samples ttest, p < .001). Students gave high ratings to all questions (all > 4.0 on scale of 1-5). Discussion Overall, the course was successful in teaching students how to respond to medical emergencies, with high effectiveness and efficacy. Future courses should continue to emphasize high-quality instructors (including resident-teachers) and small-group design, but should decrease repetitiveness and inconsistency in content.